Mechanisms of horseradish peroxidase and α-chymotrypsin. (1st June 2013) - Dunford, H. Brian
The pH range for Compound I formation of horseradish peroxidase (2.5 to 11) is the largest for any known enzyme reaction. A key part of the reaction is proton transfer from hydrogen peroxide to distal His42. This proton is retained to complete formation of a water leaving group as the ferryl porphyrin π-cation radical is formed. How can the imidazolium side chain of His42 retain a proton at very high pH? And how can it give up the proton when required at very low pH? The answer is rearrangement of electronic charge through Electron Density Circuits (EDCs) in the protein matrix. An increase of at least 9 pKa units, which occurs on the imidazole side chain of His42 as the Compound I reactive intermediate is formed, is facilitated by an EDC. A reverse EDC facilitates proton transfer to form the water leaving group. The pathway of the EDC involves the heme, its propionate side chains, Arg41, and His42. The occurrence of EDCs in chymotrypsin reactions reinforces the nucleophilic attack, and the subsequent electron and proton transfers. They also can shift pKa values. The catalytic triad of chymotrypsin is Ser195, His57, and Asp102. The currently accepted one-proton transfer mechanism involves Ser195 and His57, with Asp102 being regarded as too acidic to accept a proton. A comparatively small shift in the pKa value of Asp102 is all that is required to make it a proton acceptor from His57 so a two-proton mechanism may occur.